The Articulation Between Employment and Social Protection Policies. A Portuguese Overview from the 1974 Revolution to the Ongoing Pandemic Crisis - Caleiras, J.; Carmo, R. M. (15th Conference of the European Sociological Association 2021. Sociological Knowledges for Alternative Futures., 2021)
This communication is a result from the ongoing Employall research project, funded by the Portuguese Foundation for Science and Technology (PTDC/SOC-SOC/30543/2017). From a critical perspective, it discusses the main guidelines of employment and protection policies in Portugal, as well as their articulation over the last five decades (from the democratic Revolution in April 1974 to the ongoing pandemic crisis caused by COVID-19). The aim is to understand the ways and misplacements of employment and protection policies, and to detect in them signs underlying Karl Polanyi's double movement process. From a methodological point of view, the various macroeconomic and political frameworks are considered, being developed a diachronic qualitative analysis of changes in employment and protection policies considering how do they approach, intersect or differ from eachother. Regarding sources, legal diplomas which regulate policies, government programmes defining policy proposals and statistical data are used to mirror the main trends. Three major phases are distinguished, composed of different political and economic cycles and the results point in a double direction. There are three main stages, consisting of different political and economic cycles, and the results point in a double direction. The long-analyzed period is crossed by moments of tension and alternation between policies, and is punctuated by two movements that, being able to coexist in time, have different meanings: a movement of social progress, which incorporates progressive values into policies; and another social backsliding movement, which carries a dominant neoliberal political matrix and has been deepening.